Carbon coated NixCoyMn1-x-yO/Mn3O4 with robust deficiencies grown on nanoporous alloy for enhanced Li-Ion storage. (1st February 2020) - Zhang, Shaofei; Zhang, Zhijia; Zhang, Xiyuan; Kang, Jianli
Abstract: Synthesis of nanostructured transition metal oxides with enriched deficiencies is a promising approach to accommodate the stress from volume changes and maximize conversion reactions. Here, we propose a rational design of carbon coated Nix Coy Mn1-x-y O/Mn3 O4 electrode with robust metal/oxygen vacancies distributing in mixed crystal structure by self-combusting a nanoporous alloy and subsequently carbon coating. With partial Mn and Co ions replacing of some Ni 2+ in NiO-basic crystal lattices, the enriched oxygen/metal vacancies build local electric field and enable enhanced Li + storage capability. Additionally, the carbon layer synergy with the residual core-alloy can enhance the electronic conductivity of oxides and accommodate the volume change efficiently. On these foundations, the carbon coated NPM@oxides electrode demonstrates excellent electrochemical performance, showing a high reversible capacity of 901 mA h g − 1  at 0.1 A g −1, and yielding high capacities of 851 mA h g − 1  at 1 A g −1 and 649 mA h g − 1  at 3 A g −1 after 200 cycles, respectively. This novel approach with low energy consumption is first used to serve as a model for the modification of nanoporous alloys, thus paving a new way to develop nanoporous metal based energy conversion devices with high-energy-density. Graphical abstract: A low-energy-consuming approach of self-combusting of nanoporous NiCoMn and subsequently carbon coating is first used to synthesize nanoporous Nix Coy Mn1-x-y O/Mn3 O4 electrode with robust deficiencies in the distinct nanocrystal lattices, providing enhanced conductivity, fast kinetics and high Li + storage capability. Image 1 Highlights: A low-energy-consuming approach of self-combusting nanoporous NiCoMn is first used to synthesize mixed oxides. It demonstrates robust deficiencies in nanocrystal lattices, building local electric field at atomic level. The carbon layer and residual alloy acts as two highways for charge transfer and cushions to buffer the volume changes.